Comparative exergy analysis of chemical looping combustion thermally coupled and conventional steam methane reforming for hydrogen production. (10th September 2016) - Fan, Junming; Zhu, Lin; Jiang, Peng; Li, Luling; Liu, Huimin
Abstract: This paper investigates the benefits of chemical looping combustion (CLC) thermally coupled with steam methane reforming (SMR) process (CLC–SMR) over conventional SMR process by means of exergy analysis. The conventional combustor of SMR is replaced by employing CLC system in order to achieve cleaner production of hydrogen through eliminating energy penalty associated with capturing CO2 from combustion flue gas and reducing exergy destruction during combustion process. The overall exergy efficiency of SMR and CLC–SMR was calculated equal to 65.2% and 71.4%, respectively, approximately 9.5% of exergy efficiency was increased from CLC–SMR. Analyses were extended to investigate the individual exergy efficiency of each component in both processes. In SMR the main parts of exergy destroyer were localized in combustor and CO2 capture unit with a contribution of 28.5% and 24.9% of the total exergy destroyed, respectively. In CLC–SMR process, the overall exergy destruction was reduced to 217.9 compared with that of 299.7 kJ per mol of CH4 used in SMR. The exergy efficiency of combustion process in SMR and CLC–SMR was calculated equal to 78.0% and 76.5%, respectively, correspondingly reducing exergy destruction from 85.3 in conventional combustor to 79.1 in CLC kJ per mol of CH4 used. A preliminarily financial analysis was involved further to examine the economic feasibility of CLC–SMR process. Highlights: Improvement of SMR process by coupling with CLC was analyzed by exergy analysis. Coupling of CLC with SMR can increase overall exergy efficiency by 9.5%. CLC–SMR process can increase combustion exergy efficiency by 3.0% from SMR process.